Management Practices Affecting Lesser Mealworm Larvae (Alphitobius diaperinus) Associated Microbial Community in a Broiler House and After Relocating With the Litter Into Pastureland - Crippen, Tawni L.; Singh, Baneshwar; Anderson, Robin C.; Sheffield, Cynthia L. (Frontiers in Microbiology, 2022)
Lesser mealworms are often found infesting production houses used to raise broiler chickens. Previous studies have investigated pathogenic microorganisms associated with the larvae, but a more thorough study relating total microbiome changes due to management procedures and flock rotations was needed. Additionally, there is a question of what microbiota are transferred into the environment when the litter, in which larvae reside, is piled in pastureland for use as fertilizer, and where interactions with the soil and other fauna can occur. This study chronicled, by16S rRNA sequencing, the bacterial community profile of larvae a broiler grow-out house synchronizing to when birds were added to and removed from the house over 2.5 yrs. The profile was found it to be relatively constant despite 11 flock rotations and management disruptions, specifically litter cleanout procedures and the addition of new birds or bedding. In contrast, once removed from the controlled broiler house environment and placed into open pastureland, the substantial microbial diversity brought with the larvae showed greater fluctuation in structure with environmental conditions, one of which was rainfall. Surprisingly, these larvae, survived at least 19 weeks, so the potential for moving larval associated microbes into the environment needs further assessment to minimize the risk of relocating foodborne pathogens and also to assess those bacteria generating metabolites that have benefits to plant growth when using the litter as a fertilizer. The characterization of their microbiome is the first step to investigating the influences of their microbes on the manmade and the environmental ecosystems.